2023
DOI: 10.1186/s42358-023-00295-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of secukinumab in ankylosing spondylitis and psoriatic arthritis: a 52-week real-life study in an Italian cohort

Abstract: Background Secukinumab has shown high efficacy in randomized controlled trials in both ankylosing spondylitis (AS) and psoriatic arthritis (PsA). Here, we investigated its real-life effectiveness and tolerability in a cohort of AS and PsA patients. Methods We retrospectively analyzed medical records of outpatients with AS or PsA treated with secukinumab between December 2017 and December 2019. ASDAS-CRP and DAS28-CRP scores were used to measure axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…Our findings demonstrated a high probability of secukinumab retention that is consistent with previous reports ( 34 , 39 , 40 , 46 , 49 , 61–63 ). The 12-month persistence rate was very similar to that obtained in EuroSpA study and the BIOBADASER Spanish registry ( 34 , 39 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings demonstrated a high probability of secukinumab retention that is consistent with previous reports ( 34 , 39 , 40 , 46 , 49 , 61–63 ). The 12-month persistence rate was very similar to that obtained in EuroSpA study and the BIOBADASER Spanish registry ( 34 , 39 ).…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, an analysis of the Spanish BIOBADASER registry (two of the 28 participating centers overlap with the present study; N = 350) reported a slightly higher 2-year remission rate (77%) but with an almost identical change from baseline ( 39 ). Similarly, in a recent real-life study, Molica Colella et al also observed that, in a population ( N = 56) that was largely naive to bDMARDs, 68% of patients achieved remission (DAS28-CRP < 2.6) by week 52 of secukinumab treatment ( 40 ).…”
Section: Discussionmentioning
confidence: 86%
“…Real-world evidence is gradually emerging from observational data, surveys, and registries ( 31 – 36 ). Our study contributes to the body of evidence, aligning with recent real-life Italian studies published on AS and axSpA ( 27 30 ).…”
Section: Discussionsupporting
confidence: 88%
“…In the context of axSpA, other RWE studies have investigated the effectiveness and safety of secukinumab in a real-life setting both in Italian ( 27 30 ) and international cohorts ( 31 – 36 ), even in comparison with TNFi ( 9 , 10 , 31 , 32 ), but only for a limited observational period. In addition, the impact of different lines of bDMARDs treatment (LoBT), axSpA subtype, and sex on the achievement of clinical remission and on secukinumab drug survival has not yet been fully investigated ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“… 7 Although IL-17A blockade has been greatly effective, remission is achieved in only a portion of AS patients (~65.5%). 8 These data suggest that AS pathogenesis can be driven by multiple disease mechanisms including those that are Th17-dependent and those that are Th17-independent.…”
Section: Introductionmentioning
confidence: 88%